Undifferentiated carcinoma of parapharyngeal space in 8 year old female child: a rare case presentation - Kadela, Ramesh; Jindal, Sonia; Arya, Pooja; Nagaraj, Niranjan; Lal, Deepchand; Lal, Deepchand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Parapharyngeal space tumors represent only 0.5% of all head and neck tumors. Out of which, 80% are benign and 20% are malignant. Tumor must be at least 2 cm in size before bulge or abnormality is palpable. We report a case of 8 year old female child who presented with bulge in right tonsillar region.